(untitled) (Research, Society and Development, 2021)
This review aims to gather evidence to identify the possible benefits of using EOs associated with physical therapy for pain relief in dysmenorrhea. To define the research question in a structured way, the acronym PICO format was used and the search process for appropriate publications was fully documented by the Preferential Reports for Systematic Reviews and Meta-Analysis (PRISMA) items. The selected articles studied the use of different EOs, either alone or in association. In addition to massage as the main technique, the use of warm compresses associated with EOs for pain relief was also found. Overall, the revised manuscripts found positive results, showing that EOs have great benefits in the treatment of PD. The use of EOs associated with physiotherapy enhances the treatment and alleviates the pain in women affected by PD. On the other hand, none of the studies mentioned or presented data about SD.